Evaluation of Railway Level Crossing Attributes on Accident Causation in Lagos, Nigeria. - Adeolu O Dina; Cornelius O Akanni; Bamidele A Badejo (Faculty of Geography, Universitas Gadjah Mada, 2016)
Abstract The study examines the contribution of Railway Level Crossing (RLC)physical attributes to accident occurrence using the12 major level crossings within the Lagos metropolis. The 48km single track mainline section under consideration which barely make up 1.1% of the entire narrow gauge track network of the country within a 5 year period contributed about 45% of the total National crossing accidents recorded in Nigeria. The method of investigation involved recording the individual attributes of each RLC such asgates, pedestrian traffic, car traffic light, proximity of signage to crossing, vehicular traffic as dummy variables.The regression analysis was used to measure their effect on accidents.The result indicates gates, pedestrians and the location of signage had significant impact on accidents occurrence at level crossings within Lagos metropolis. Based on the findings, enhancement of active warning systems among other recommendations was suggested as potent counter measures for RLC accident reduction.Abstrak Penelitian menguji tingkat kontribusi atribut fisik dari perlintasan jalan kereta api terhadap kejadian kecelakaan menggunakan 12 perlintasan utama dalam kota metropolis Lagos. 48 km jalan utama tunggal menjadi pertimbangan yang hampir meningkat 1.1% dari seluruh trek sempit jaringan negara dalam jangka waktu 5 tahun menyumbang sekitar 45% dari total kecelakaan perlintasan secara Nasional di Nigeria. Metode penelitian melibatkan catatan dari masing-masing atribut RLC seperti pintu gerbang, pejalan kaki, lampu lalu lintas mobil, kedekatan tanda penyebarangan, lalu lintas kendaraan sebagai variabel dumi. Analisis regresi digunakan untuk mengukur pengaruh dari atribut terhadap kecelakaan. Hasilnya menunjukkan pintu gerbang, pejalan kaki, dan lokasi tanda perlintasan mempunyai dampak signifikan pada kecelakaan dalam kota metropolis Lagos.Berdasarkan penemuan tersebut, perbaikan dari sistem peringatan aktif disarankan sebagai upaya mengurangi kecelakaan RLC.